If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 = 5x + -3 Reorder the terms: 3 + 2x = 5x + -3 Reorder the terms: 3 + 2x = -3 + 5x Solving 3 + 2x = -3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 3 + 2x + -5x = -3 + 5x + -5x Combine like terms: 2x + -5x = -3x 3 + -3x = -3 + 5x + -5x Combine like terms: 5x + -5x = 0 3 + -3x = -3 + 0 3 + -3x = -3 Add '-3' to each side of the equation. 3 + -3 + -3x = -3 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = -3 + -3 -3x = -3 + -3 Combine like terms: -3 + -3 = -6 -3x = -6 Divide each side by '-3'. x = 2 Simplifying x = 2
| S=4k+4w | | -3(x-2)=16 | | t^2-2t-120=0 | | 3x+x=130 | | 3(n+5)+2=60 | | 4w-6= | | .20*40= | | n^2=6n+72 | | b/4+5=14 | | x+y=130 | | a/9=6 | | -7=11+x | | 2x-5x=-6 | | 3*76= | | (9x-81)=12 | | 34/6=2x+1/3 | | 3x^2-2x-12x+8= | | 3x+y=130 | | 6y=30y+140 | | 2abc+d=3 | | -5y-2y+3y=9 | | -19-(-4)=x | | -10-(-5)=x | | -18=6x-4x | | 3/4=z/16 | | 2a+-5b+5a+-1b= | | c^2=40-3c | | 8x-9+7x= | | 55=5/9(f-32) | | 7-3x=5x | | 2a-7=1 | | 3(x+3)=4(x-1) |